Доклад о торговле и развитии 2024 - UN Trade; Development (United Nations, 2025)
The Trade and Development Report 2024 forecasts global growth in gross domestic product of 2.7 per cent for 2024 and 2025, marking three consecutive years below the 3 per cent pre-pandemic growth trend. Regionally, South Asia displays the most dynamic growth. The three major powers of the global economy – China, the United States of America and the European Union – are on decelerating or weakened growth trajectories. Despite the context of a turbocharged technological revolution, the much-needed acceleration in economic activity to achieve the Sustainable Development Goals remains elusive for many countries in the global South trapped by a confluence of high debt burdens, financial and resource outflows, weak investment and enforced austerity. Only 1 of the 46 least developed countries is currently meeting the promise of a 7 per cent annual growth target under the global Goals.